Analytical Method Validation of Sulfamethoxazole in Human Plasma and Urine by HPLC-PDA - Dion Notario; Aprillia Suwita; Kelviyana Kelviyana (Jurnal Sains dan Kesehatan, 2022)
An analytical method for analyzing SMZ in human plasma and urine using high-performance liquid chromatography (HPLC) was developed. The separation was carried out on a Shim-pack GIST® C18 column (150 × 4.6 mm, 5 ?m) with a temperature setting of 30°C. The mobile phase consisted of glacial acetic acid pH 2.5: methanol: acetonitrile (70:25:5, v/v/v) at a rate of 0.8 mL/min. Detection was done using a PDA detector in the range of ?190-800 nm, and quantification was carried out at ?265 nm. Plasma sample preparation used the protein precipitation method with acetonitrile as the precipitating solvent (1:3, v/v), while urine preparation used the liquid-liquid extraction method with 0.03 M H2SO4 and ethyl acetate. The developed method was proven selective, linear (r = 0.998) for plasma and (r = 0.996) for urine, accurate (%error ?11.76% for LLOQ and ?14.08% for concentrations above), precision (%RSD ?4.52% for LLOQ and ?4.48% for the concentrations above), sensitive with 0.7 ?g/mL (plasma) and 0.17 ?g/mL (urine). Stability tests were carried out to determine the shelf life of the samples under several conditions. The developed method is valid and suitable for pharmacokinetic studies of SMZ in human plasma and urine.